Classificação arquivística: uma proposta de plano de classificação documental para Agência de Regulação de Serviços Públicos do Estado do Pará (ARCON-PA) - SILVA, Elidiane de Nazaré Viana e (2017)
It is proposed to discuss the classification concept in archive science through a theoretical / practical approach. We realize that in the classification of documents there are still misconceptions when we think of their practical applicability in the archives. Thus, we intend through an exploratory research and a qualitative approach, to propose a filing plan/system for the documents Department Road Transport Technical Group (GTT) Subsection “cadastro”, of the Public Services Regulation Agency of the State of Pará (ARCON-PA).Given this, we aim to understand one of the points of records management, classification. Thus, it is theoretically based on Gonçalves (1998), Jardim (2015, 1987), Sousa (1995, 2006, 2013, 2014) among other authors with relevance to the theme. We conclude that classification is a fundamental procedure for the treatment, dissemination and retrieval of information.